A Study of Deaf Community and Its Impact on Children with Deafness: A Systematic Review (Journal of Asian Development Studies, 2023)
This study explores the impact of the deaf community on children with deafness and examines the social and developmental benefits that are from being a part of a supportive and inclusive deaf community. This study also discussed the factors that contribute to the positive impact of community involvement, including language acquisition identity development and access to resources. This also investigates the influence of the deaf community on children with deafness within the context of the Pakistani population, employing descriptive research methodologies. A cohort of 50 children with hearing impairment, primarily adolescents, sourced from prominent institutions in Lahore, Pakistan, was examined. Data collection was conducted through parental surveys, revealing that 17 of the children were integrated into the deaf community. Employing a standardized 34-questionnaire instrument, data was processed using SPSS version 10. The findings underscore a substantial positive impact of the deaf community on the overall rehabilitation of these children. This study advocates for a community-centric approach to rehabilitation, emphasizing the vital role of parental support and character development. Moreover, it stresses the importance of embracing the disability and cultivating a constructive mindset among the children. To actualize these recommendations, fostering leadership opportunities through organized events such as sports, entertainment programs, seminars, and workshops is encouraged.